PENGARUH PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT DAN PENGUNGKAPANINTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan-perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia pada Periode Tahun 2015-2018) - Muhammad Rizki Mabrur; Surya Raharja (Diponegoro Journal of Accounting, 2021)
The purpose of this study is to examine the effect of enterprise risk management disclosure and intellectual capital  disclosure on firm value in mining companies in Indonesia.The population in this study were all mining companies listed on the Indonesia Stock Exchange for the year 2018. The sampling method used in this research was purposive sampling. The total number of samples in this study were 38 companies that were the research samples. The data used in the study were obtained from the company's annual reports. The data in this study were analyzed using the classical assumption test before the data was tested using panel data regression test. The results of this study indicate that enterprise risk management disclosure has a positive and significant effect on firm value. Meanwhile, disclosure of intellectual capital  has no effect on firm value.